2012
DOI: 10.1007/s00384-012-1413-y
|View full text |Cite
|
Sign up to set email alerts
|

Early complications after stoma formation: a prospective cohort study in 100 patients with 1-year follow-up

Abstract: In this heterogenic patient population with formation of different stoma types, a high complication rate was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 14 publications
(20 reference statements)
5
52
1
2
Order By: Relevance
“…This incision has been associated with chronic abdominal pain because of nerve entrapment . Although we reported a higher rate of stoma‐related complications in our study (81%), our results are similar to a study by Formijne Jonkers et al . They included 100 adult patients who underwent intestinal stoma formation for different indications (e.g., colorectal malignancies, complicated diverticulitis, inflammatory bowel disease, anastomotic leakage) and reported that 82% of adult patients had one or more stoma‐related complications.…”
Section: Discussionsupporting
confidence: 89%
“…This incision has been associated with chronic abdominal pain because of nerve entrapment . Although we reported a higher rate of stoma‐related complications in our study (81%), our results are similar to a study by Formijne Jonkers et al . They included 100 adult patients who underwent intestinal stoma formation for different indications (e.g., colorectal malignancies, complicated diverticulitis, inflammatory bowel disease, anastomotic leakage) and reported that 82% of adult patients had one or more stoma‐related complications.…”
Section: Discussionsupporting
confidence: 89%
“…Superficial necrosis is observed in 2%–20% of the patients, and deep necrosis is observed in 0.37%–3%. 11 14 The bowel prepared for ostomy to prevent ischemia should be able to move easily up to the place where it will exit the skin, and the vascularity of the bowel should not be disrupted during this process. Epiploic fat and mesentery should not be damaged too much.…”
Section: Discussionmentioning
confidence: 99%
“…These complications were diagnosed according to standard predefined criteria and were based on those occurring most frequently2, 4, 16, 17, 18, 19, 20, 21, 22. General postoperative complications were recorded, including surgical‐site infection, abdominal abscess, ileus, abdominal fascia dehiscence, anastomotic leakage, pneumonia, urinary tract infection and a miscellaneous (other) group.…”
Section: Methodsmentioning
confidence: 99%